Literasi informasi generasi x, y, dan z dalam penyusunan karya tulis ilmiah Universitas Diponegoro - Rizki Nursistian Fitri; Yanuar Yoga Prasetyawan (Jurnal Kajian Informasi dan Perpustakaan, 2020)
Diponegoro University (UNDIP)’s vision is “Diponegoro University Becoming a Superior Research University," which implies that every academician at UNDIP requires improving research through scientific papers. Scientific writing is a work that the author must account for morally or intellectually. Consequently, it needs to conduct observation, planning, directed search, finding information, using information, and evaluating information through information literacy. This study aimed to determine the information literacy generation x, y, and z in the preparation of scientific papers at UNDIP. The research used a qualitative method with a phenomenological approach. The data collection technique used deep interview and observation. The analysis showed that information literacy had an essential role for generation x, y, and z in the preparation of scientific papers. Information literacy activities are a form of one's accountability when dealing with information for the needs of scientific writing. The three generations conducted information literacy activities during the scientific paper preparation. This can be seen from the activities carried out, namely the identification of scientific information needs, scientific information retrieval, scientific information utilization, and scientific information communication. In the current era of technological development, generation x, y, and z, which have unique characteristics in the preparation of scientific papers. Hence, information literacy is used as a standard. Each generation have skill information literacy so must account scientific writing have been written.